2001
DOI: 10.1071/bt00020
|View full text |Cite
|
Sign up to set email alerts
|

Germination of dimorphic seeds of Suaeda moquinii under high salinity stress

Abstract: Suaeda moquinii (Torrey) Greene (desert blite), a succulent shrub in the family Chenopodiaceae, is widely distributed in salt marshes of the western United States. Suaeda moquinii produces dimorphic seeds (soft brown and hard black). Both types of seeds were collected from a salt marsh in Faust, Utah. Experiments were conducted to determine the seed germination responses of the black and brown seeds to salinity and temperature. Brown seeds were found to be one of the most salt tolerant at the germination stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 30 publications
3
26
1
5
Order By: Relevance
“…It was reported that above 10% chromosomal irregularities in higher doses in Clotaria juncea and Clotaria sericea due to treatment with gamma ray [21]. Although other authors observed that the percentage of abnormalities was increased with an increase of the gamma rays in Crotalaria juncea and Clotaria sericea [17,22]. Similar result was also noticed in tetraploid and hexaploid wheat [23].…”
Section: Resultssupporting
confidence: 69%
“…It was reported that above 10% chromosomal irregularities in higher doses in Clotaria juncea and Clotaria sericea due to treatment with gamma ray [21]. Although other authors observed that the percentage of abnormalities was increased with an increase of the gamma rays in Crotalaria juncea and Clotaria sericea [17,22]. Similar result was also noticed in tetraploid and hexaploid wheat [23].…”
Section: Resultssupporting
confidence: 69%
“…Seed dimorphism and polymorphism are reported in many halophytic species including Arthrocnemum, Chenopodium, Atriplex, Cakile, Salicornia, Salsola, Spergularia, and Suaeda growing under saline conditions (Khan and Ungar 1984a, b;Mohammad and Sen 1988;Myers and Morgan 1989;Ungar 1991;Khan et al 2001Khan et al , 2004. S. salsa produces brown and black seeds on the same plant; this appears to a useful strategy to increase chances for population establishment under variable temperatures and soil salinities (Ungar 1995).…”
Section: Discussionmentioning
confidence: 97%
“…The limits of salt tolerance vary somewhat among species of succulent halophytes with some seeds of the leaf succulents S. moquinii (30% germination at 100 mM NaCl; Khan et al 2001), and S. linearis (1% germination at 100 mM NaCl) germinating in up to 849 mM NaCl (Ungar 1962(Ungar , 1967 while others like Arthrocnemum indicum (3% germination at 100 mM NaCl) can germinate in 1,000 mM NaCl . There are reports of other species (Salicornia bigellovia, S. europaea, S. pacifica) indicating some germination at NaCl concentrations above 800 mM (Rivers and Weber 1971;Ungar 1979;Khan and Weber 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the ability of the ungerminated seeds in saline solutions to recover their germination capacity after being transferred to distilled water is known to be very low in certain halophytes such as Zygophyllum simplex (Khan and Ungar, 1997), Halogeton glomeratus (Khan et al, 2001) and Sporobolus ioclades (Khan and Gulzar, 2003), suggesting they have greater sensitivity to the higher salinities. Seeds of halophytes that are more sensitive to higher salinity are more likely to die when stored in saline soils.…”
Section: Introductionmentioning
confidence: 97%